(untitled) (BIRDEM Medical Journal, 2025)
Background: Capillarization of sinusoids occur in hepatocellular carcinoma (HCC) and several studies showed these altered sinusoids become immunoreactive for CD34. HCC and some non-malignant hepatic nodules mimic microscopically. The aims of this study were to find out the location and pattern of CD34 expression in HCC and non-malignant hepatic nodules and to see whether CD34 expression can differentiate them. Methods: This cross-sectional study was conducted in the Department of Pathology, BIRDEM General Hospital, Dhaka from March 2020 to February 2022. Thirty-one cases of HCC and 31 cases of non-malignant hepatic nodules were included in this study. Detail microscopic examinations were done regarding HCC, its morphological type, grade, cirrhosis, dysplasia and of other type of non-malignant hepatic nodules. Immunohistochemical staining of CD34 was performed in all cases. Results: No sinusoidal expression of CD34 was found in normal hepatic tissue. In benign hepatic nodules, sinusoids showed none to up to 20% areas of sinusoidal expression with +/++ intensity. HCC showed expression of CD34 in more than 50% areas with an intensity of +++ irrespective of grade and morphological type. Extent of CD34 expression increased significantly with the increasing grade of tumor. In cirrhosis, CD34 expression significantly increased in dysplastic than non-dysplastic cirrhotic nodules. Conclusion: The extent of expression became significantly increased from low grade dysplasia and more significantly increased in HCC than non-malignant hepatic nodules. BIRDEM Med J 2025; 15(1): 22-27